1975
DOI: 10.1128/jcm.1.5.411-413.1975
|View full text |Cite
|
Sign up to set email alerts
|

Use of cetylpyridinium chloride and sodium chloride for the decontamination of sputum specimens that are transported to the laboratory for the isolation of Mycobacterium tuberculosis

Abstract: A method is presented for the decontamination, liquefaction, and concentration of sputum specimens that are in transport more than 24 h. The method is inexpensive, and culture results compare well with those obtained with the accepted N-acetyl-L-cysteine and sodium hydroxide method for the isolation of tubercle bacilli. The working solution, 1% cetylpyridinium chloride and 2% sodium chloride, is mixed in equal volumes with sputum before the specimens are shipped. Tubercle bacilli remained viable after 8 days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 2 publications
0
32
1
Order By: Relevance
“…The quaternary ammonium compounds CPC and cetyltrimethylammonium bromide achieved less than 10-fold reductions in GNB populations in the 10-min exposure time. Additional studies with CPC showed that, even at concentrations of 500 and 1,000 ,ug/ml, 30and 15-min exposure times, respectively, were required to obtain greater than 100-fold reductions in viable counts of GNB. Moreover, at these higher concentrations of CPC, up to 100-fold reductions in viable counts of some M. chelonae and MCLO strains also were observed.…”
Section: Resultsmentioning
confidence: 99%
“…The quaternary ammonium compounds CPC and cetyltrimethylammonium bromide achieved less than 10-fold reductions in GNB populations in the 10-min exposure time. Additional studies with CPC showed that, even at concentrations of 500 and 1,000 ,ug/ml, 30and 15-min exposure times, respectively, were required to obtain greater than 100-fold reductions in viable counts of GNB. Moreover, at these higher concentrations of CPC, up to 100-fold reductions in viable counts of some M. chelonae and MCLO strains also were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Du Moulin & Stottmeier (1978) used cetylpyridinium chloride (0-02-1.0%, 24 h) to decontaminate water, and Smithwick et al (1975) reported using it for the suppression of contaminants in sputum specimens, at approximately 0.6% in combination with sodium chloride. Recently, Jaramillo & McCarthy (1986) tested the recovery of M. auium from buffer in the presence of soil, following a 60-min exposure to 0.04% cetylpyridinium chloride at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Growth of M. auium on Lowenstein-Jensen medium when often no growth could be obtained on Middlebrook 7H10 plates may indicate that washing after decontamination may not have been suficient. Residual amounts of the two detergents may have inhibited growth in 7H10 media, but would have been neutralized by the egg medium (Smithwick et al 1975). Possibly, any carry-over of Tween 80 in combination with the antibiotics in the Middlebrook medium could have acted as a further inhibitor to M .…”
Section: Discussionmentioning
confidence: 99%
“…If refrigeration is not possible, samples should be treated first with equal volume of 0.6% cetylpyridinium bromide or 1% cetylpyridinium chloride in 2% sodium chloride, which reduces the survival of contaminating microorganisms while preserving the viability of M. tuberculosis for up to 8 days. [24][25][26] Although the recovery of fungi is optimal from cultures of fresh specimens, most clinically significant fungi appear to survive storage of 16 days or longer. 27 Specimens for viral cultures should be shipped refrigerated but not frozen, whereas specimens for chlamydial culture should be placed into sucrose phosphate medium and shipped frozen.…”
Section: Specimen Adequacymentioning
confidence: 99%